Embedded Online Questionnaire Measures Are Sensitive to Identifying Mild Cognitive Impairment. (April 2016) - Seelye, Adriana; Mattek, Nora; Howieson, Diane B.; Austin, Daniel; Wild, Katherine; Dodge, Hiroko H.; Kaye, Jeffrey A.
Abstract : Background/Aims: Early changes in cognitively demanding daily activities occur between normal cognition and the development of mild cognitive impairment (MCI). These real-world functional changes as early signals of cognitive change form a prime target for meaningful early detection of dementia. We examined whether passive aspects of responding to a remotely monitored weekly online questionnaire discriminated between older adults with and without MCI. Methods: Participants were 83 independent, community-dwelling older adults enrolled in a longitudinal study of in-home monitoring technologies, which included completion of a short weekly online questionnaire of health and life events. Results: In longitudinal analyses, time to complete the online questionnaire decreased over 1 year in both MCI and cognitively intact participants ( P <0.01). MCI and intact participants did not differ in the time of day they submitted their questionnaires initially; however, over the course of 1 year MCI participants began to submit their questionnaires progressively later in the day and they needed greater assistance from staff as compared with intact participants ( P <0.05). The online questionnaire performance measures were significantly correlated to conventional cognitive test scores ( P <0.05) across the spectrum of normal cognition to MCI. Conclusions: Ambiently assessed, passive performance measures embedded within an online questionnaire are able to discriminate between normal cognition and MCI. Remote monitoring of cognitively demanding routine daily activities is a promising approach for ecologically valid real-world cognitive assessment.